موقف النخبة الجزائرية من التجنيد الإجباري -1907-1918 عبد الحليم بن سماية –أنموذجا - دعاء سبع; راوية دباخ (جامعة الوادي - University of Eloued, 2025)
تهتم هذه الدراسة بجانب من جوانب السياسة الإستعمارية في الجزائر ، المتمثل في موضوع تجنيد الشباب الجزائري من خلال تسليط الضوء على موقف و جهود أحد الشخصيات النخبوية الرافضة و المعارضة للقانون ألا و هو عبد الحليم بن سماية فكان من ابرز الشخصيات التي تصدت لسياسة التجنيد الاجباري في الجزائر مؤكدا على ضرورة الحفاظ على الهوية الدينية و السياسية للأمة الجزائرية ، من خلال مواقفه الجريئة و الصارمة رفقة معاصريه من النخبة الجزائرية أمثال عمر راسم عمر بن قدور و عبد القادر مجاوي حيث تباينت مواقف الجزائريين من رافض و مؤيد الامر الذي خلف ردود فعل متباينة في الأوساط الجزائرية و الفرنسية. This studufocuses on an aspect of the colonial policy in algeria namely the recruitment of algerian youth the law of february 3,1912, bay highlighting the stance and efforts of one of the brominet elite figures who obbosod and rejocted the censcribtion law-Abdalhlim Ben smayah, he was among the most notable individuals who stood against the policy of mandatory military service in Algeria em bhasizing the imbortance of preserving the religieus and political identity of the Algerian nation, throgh his pold and firm positiens, along with thos of his contemporaries ameng the Algerian elite-such as Omar Racim, Ben Kaddour, and Al-Majawi -the Algerian response varied, with some supperting and otherc opposing the policy, this divergence sparked a range of reactions within both Algerian and french circles.
مذكرة ماستر قسم علوم انسانية تخصص تاريخ المغرب العربي المعاصر
Keywords: عبد الحليم بن سماية; التجنيد الإجباري; موقف النخبة; The position of the elite; compulsory conscription; Abdel Halim Ben Samaya